Blockchain technology for Islamic social impact investment and its applicability in Malaysia’s green energy sector - Adam Sa'ad, Auwal; Puteri Hanie Shahirah, Binti Noorhelmee; Nurulhuda binti, Md Nazar; Beytullah, Aydin (2021)
Mudaliar, Bass, Dithrich, and Nova (2019) defined impact investment as an “investment made to generate positive, measurable, social and environmental impact alongside a financial return”. Based on a survey by the Global Impact Investing Network (GIIN), a total of USD 35.5 billion was invested and 11,136 deals were closed related to social impact investment in 2017 (Coulter, 2020). In order to achieve the United Nation Sustainable Development Goals 2030 (UN DSGs 2030) for sustainable financial inclusion, Bank Islam Malaysia Berhad (BIMB) integrates environmental, social, and governance (ESG) criteria in their investment portfolio, as well as leveraging the benefits of investment using robo-advisory to attract retail investors (DinarStandard, 2020).